New economy accounting : why are broad-based stock option plans so attractive? - Dieter E. Hess; Erik Lüders (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
Several studies indicate that stock option plans are becoming more and more a substantial part of compensation schemes in U.S. companies. This paper shows the tax implications and accounting rules for stock option plans. By comparison of the tax and accounting rules for different compensation schemes we show that the popularity of stock options may be mainly due to the U.S. Generally Accepted Accounting Principles (US-GAAP) which require no charge to earnings for speciffically designed stock option plans if a company opts for footnote disclosure. Thus, for these companies the stated earnings are higher than their economical situations justify. Based on a case study of 20 companies out of the S&P 500 which rely heavily on employee stock options we arrive at the conclusion that the amount of hidden compensation cost can reach economically signifficant amounts. Since this topic seems to be widely neglected it is questionable whether stock prices reflect these hidden cost.
Keywords: G0; M41; 330; Accounting; US-GAAP; stock option programs; Leistungsorientierte Vergütung; Aktienoption; Steuer; Bilanzierung; Grundsätze ordnungsmäßiger Buchführung; Verdeckte Gewinnausschüttung; USA; hidden compensation